الإدارة الموقفية في المنظمات الادارية الحديثة - حدار, جمال (revue mofakir, 2018)
Abstract : Due to the accurent development in technology and the co-relation between the external ,internal ,political, economical ,social and environmental .also as a result to increasingly appearance of risks, catastrophes and crises. Although, the accurent development in all fields, the harmful phenomena steal causing human and material lots. Thus, most of the organizations seek to find new and effective mechanisms to adapt and manage new situations with possible cost, and maintain the balance in harsh and unprecedented conditions.   الملخص : ما يميز المنظمات الحديثة هو العمل في بيئة مفتوحة على كل المجالات ،نظرا للتطور الحاصل في التكنولوجيا والترابط بين ما هو داخلي وخارجي وما هو سياسي واقتصادي واجتماعي وبيئي ،وكذا لظهور المخاطر والكوارث والأزمات بشكل متزايد ،وبالرغم من التطور الحاصل في كل الميادين إلا أن الظواهر الضارة لازالت تخلف خسائر مادية وبشرية وبالتالي أصبحت معظم المنظمات تسعى لإيجاد آليات فعالة للتكيف وإدارة المواقف المستجدة بأقل التكاليف الممكنة والحفاظ على توازنها في ظروف قاسية وغير مسبوقة .